2008
DOI: 10.1111/j.1399-3038.2007.00586.x
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusskin colonization in atopic dermatitis children is associated with decreased IFN‐γproduction by peripheral blood CD4+and CD8+T cells

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disorder, which is associated with an increased expression of Th2 cytokines with concomitant decrease in IFN-gamma production by circulating CD4+ and CD8+ T cells. The skin of patients with AD is often colonized by Staphylococcus aureus, which may reflect in changes in immunological parameters. The aim of the study was flow cytometric measurement of some peripheral blood lymphocyte subsets expressing naive/memory marker (RA/RO) and activation marker (CD25) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 42 publications
0
23
2
1
Order By: Relevance
“…Our findings confirmed that 21% of elderly patients had AD with low total IgE and were not allergic to common allergens. These values are slightly higher than those of other reports (5–15%), which have investigated younger populations [9,14,15]. It is possible that AD with low total IgE is more prevalent in elderly AD patients.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Our findings confirmed that 21% of elderly patients had AD with low total IgE and were not allergic to common allergens. These values are slightly higher than those of other reports (5–15%), which have investigated younger populations [9,14,15]. It is possible that AD with low total IgE is more prevalent in elderly AD patients.…”
Section: Discussioncontrasting
confidence: 54%
“…Blood lymphocyte profiles were measured via the whole-blood method using fresh 10-ml EDTA blood samples according to Machura et al [9]. The following lymphocyte markers were measured using ImmunoGEN kits (BD Bioscience) and a FACSCanto II flow cytometer (Becton Dickinson): CD3, CD29, CD1656, CD4, CD8 and HLADR.…”
Section: Methodsmentioning
confidence: 99%
“…Teramoto et al showed a reduced ability of IFN-g production by PBMCs was associated with an elevated serum IgE levels in AD [33]. Mauchra et al found that decreased INF-g production by peripheral blood in AD children was negatively correlated with the number of skin colonization of Staphylococcus aureus and SCORAD index [34]. Meanwhile, Kä llströ m et al showed the decrease in IFN-g + cells did not necessarily correlate with the serum levels of IgE [35].…”
Section: [ ( ) T D $ F I G ]mentioning
confidence: 95%
“…77 Furthermore, an inverse relationship between skin colonization with S aureus and spontaneous T cell-derived IFN-g production has been observed. 78 Biphasic T H 2-T H 1 cytokine skin response. Acute AD skin lesions are associated with the infiltration of T H 2 cells expressing increased levels of IL-4, IL-13, and IL-31, a pruritogenic T H 2 cytokine that correlates with severity of AD.…”
Section: Skin Barrier Dysfunctionmentioning
confidence: 99%